Developing resilient graduates to be future workplace leaders. Issue 1 (6th May 2020) - McQuillan, Nikki; Wightman, Christine; Moore, Cathy; McMahon-Beattie, Una; Farley, Heather
Abstract : Purpose: Vocational higher education and skills are recognised as key factors in shaping an economy to adapt to fast-emerging business models that disrupt workplace behaviours. Employers require graduates to be "work-ready", emphasising the need to demonstrate resilience, as a critical desired behaviour (CBI, 2019). This case study shares the integrated curriculum design, co-creation and operationalisation of "Graduate Transitions" workshops that were piloted in a compulsory final-year module across a number of programmes in a higher education institutions' business faculty to enhance graduates "work readiness". Design/methodology/approach: The collaboration and leadership thinking of industry professionals, academics and career consultants designed and co-created a workshop that enhances transitioning student resilience and prepares them for their future of work. Action research gathered data using a mixed-methods approach to evaluate student and stakeholder feedback. Findings: Evidence indicates that the workshops actively embed practical coping strategies for resilience and mindful leaders in transitioning graduates. It assures employers that employability and professional practice competencies are experienced by transitioning graduates entering the future workplace. Research limitations/implications: Limitations to this research are clearly in the methodology and concentrating on the co-creation of an innovative curriculum design project instead of the tools to accurately evaluate the impact in a systematic manner. There was also limited time and resource to design a more sophisticated platform to collect data and analyse it with the imperative academic rigour required. Emphasis on piloting and operationalisation of the intervention, due to time and resource restrictions, also challenged the methodological design. Practical implications: The positive feedback from these workshops facilitated integration into the curriculum at an institution-wide level. This paper shares with the academic community of practice, the pedagogy and active learning design that could be customised within their own institution as an intervention to positively influence the new metrics underpinning graduate outcomes. Originality/value: This pioneering curriculum design ensures that employability and professional practice competencies are experienced by graduates transitioning to the workplace.